The Mollusca Collection of the University of São Paulo Museum of Zoology: an overview and perspectives - Cavallari, Daniel C. (2017)
CAVALLARI, D. C. et al. The Mollusca Collection of the University of São Paulo Museum of Zoology: an overview and perspectives. Arquivos de Ciências do Mar, Fortaleza, v. 49, Supl., p. 40-45, dez. 2016.